Stage management - Stern, Lawrence, 1935-; Gold, Jill (Focal Press, Taylor & Francis Group, 2022)
"Now in its twelfth edition, Stage Management is the comprehensive go-to manual on stage management in all theatre environments. Revered as the authoritative resource for stage management, this text is rich with practical resources, including checklists, diagrams, examples, forms, and step-by-step directions. In addition to sharing their own expertise, Stern and Gold have gathered practical advice from working stage managers of Broadway, off-Broadway, touring companies, regional, community, and 99-seat Equity waiver theaters. This new edition has been fully updated with new technology and best practices, including: - New websites for stage management tools and software - Updated Equity rules - Additional safety and emergency protocols - New voices from practicing stage managers in text boxes and case studies scattered throughout the book. This practical guide is written for students of Stage Management in Theatre programs, as well as early career stage managers. The companion website features paperwork templates, downloadable checklists, additional exercises, suggested readings, a list of websites and apps with today's cutting-edge stage management technology, and a list of over 500 internships and apprenticeships available across the United States"--